The Relationship between Religion and Politics in the Letters of Ardeshir Babakan and Niccolo Machiavelli - Sara Najafpour; ali TadayyonRad; Najmedin Gilani (رهیافتهای سیاسی و بین المللی)
The truth and nature of the relationship between religion and political power is one of the important issues regarding the system of political thought and action of the Sassanid period. This research is a preliminary attempt to more accurately evaluate the complex and multifaceted relationship between politics and religion in the political thought of Sassanid Iran with a comparative analysis of the relationship between religion and politics in the book of Ardashir and Machiavelli's views. In this article, with a comparative method and also using Skinner's method in understanding the internal logic of texts, we have studied the treatise of Ahd-e-Ardashir  focusing on its religious-political ideas in accordance with Machiavelli's views on The prince and Discourses. Our study shows that if we measure the "political functions of religion", "the necessity of rearranging religion" and "the precedence of expediency over morality" in Machiavelli's view of the relationship between religion and politics, Ardashir's covenant includes all these elements in the view of religion in politics. And therefore this work can be considered as a theoretical plan of how and the minutes of the relationship between religion and politics. Ardeshir had thought in practice and opinion from the very beginning of unifying the Iranians using the tools of religion and its details, but due to the lack of intellectual and historical background, he could not be a theorist of the transition like Machiavelli.